Measuring and enhancing organisational creative climate, knowledge sharing, and innovative work behavior in startups development. Issue 4 (17th October 2019) - Munir, Rosintansafinas; Beh, Loo-See
Abstract : Purpose: The purpose of this paper is to examine the role of the organizational creative climate, knowledge sharing and innovative work behavior in startups development. This study also aims to discover the R square, predictive relevance and effect size of the developed model. Design/methodology/approach: A quantitative method was used, and a total of 352 usable questionnaires were collected from employees at startups particularly in services sector in Malaysia. The structural equation was developed to explain the complicated relationship between organizational creative climate, knowledge sharing and innovative work behavior. The results of hypothesis were analyzed using structural equation modeling – partial least square (SEM-PLS) test. Findings: The results indicate that organizational creative climate significantly influence innovative work behavior ( H1 ), organizational climate positively affects knowledge sharing ( H2 ) and knowledge sharing significantly influence innovative work behavior ( H3 ). In addition, the results also show that the R square values of innovative work behavior is weak ( R 2 = 0.067), while the predictive relevance value demonstrating the model has sufficient predictive relevance. Further, the results of effect size show medium effect for organizational creative climate and knowledge, while the remaining indicates small effect size. Practical implications: This study provides a comprehensible and clear understanding on how organizational creative climate and knowledge sharing play important role in fostering the individual innovative work behavior in Malaysian startups. Originality/value: Research on the significance of organizational creative climate, knowledge sharing and to innovative work behavior particularly in the startups context has not been sufficiently explored. This study shed new light to the startups eco-system stakeholders in stimulating individual innovative work behavior through the practices of sharing information as well as the creative climate and innovative elements in the entrepreneurial activities.